Avaliação de cultivares de trigo à giberela - Lima, Maria Imaculada Pontes Moreira (2012)
Fusarium head blight (FHB) has the main causal agent Gibberella zeae (Fusarium graminearum) that affects spikes and wheat grains. Besides yield reduction, the disease compromises technological quality and affects human and animal health, mainly due to mycotoxins produced, and disease control is a challenge for world wheat production. Integrated actions such as the use of fungicide, cultivar with better degree of resistance and sowing scheduling are some research focus. The objectives were to evaluate the effects of sowing dates and the degree of genetic resistance of FHB in cultivars; to quantify mycotoxins in stored grains of wheat cultivars; to determine the incidence of the pathogen F. graminearum in asymptomatic grain; and evaluate the progress of the disease occurring naturally in the field. For this, ten Brazilian wheat cultivars were sown in three seasons, in Passo Fundo, RS, in 2008 harvest, in factorial randomized block design 10x3. Samples of 100 green ears were evaluated for the incidence and severity of FHB. In grain samples, troublesome percentage in 1,000 grains was determined, visually. Deoxinevalenol, fumonisin B1 and B2, zearalenone and nivalenol mycotoxins were quantified in samples of milled grains in all cultivars, two months after the harvest. Later, deoxinevalenol, nivalenol and zearalenone were analyzed in milled grains of BRS Guamirim, BRS Guabiju and Frontana cultivars at 5, 8, 11 and 14 months of storage. Incidence of F. graminearum in asymptomatic grains was determined in culture medium during the storage. The disease progress was carried out on the field in 45 spikes of BRS Guamirim and Frontana cultivars, periodically, from an affected spikelet. The intensity of the disease in spikes and grains and the incidence of the pathogen in asymptomatic grains varied according to sowing date and cultivars. Fumonisin mycotoxin was not detected and the levels of the others varied with sowing date and grain storage. Deoxynivalenol was detected in all cultivars at sowing dates and storage. Nivalenol was found less frequently and, in general, the levels of deoxynivalenol and zearalenone varied with cultivar and sowing date. Probably due to the maximum troublesome grain recovery to evaluate resistance of cultivars, in many mycotoxicological analyzes, the levels of mycotoxins exceeded the maximum tolerated by the Brazilian legislation, established in 2011. In evaluating the progress of FHB the number of points of infection ranged from 1 to 3 in both cultivars and the average values of severity were higher in cultivar Frontana, independent of the number of infection points.